Analisis atas Pembiayaan Ekspor Nasional Syariah pada Lembaga Pembiayaan Ekspor Indonesia - Moh. Luthfi Mahrus; Ivan Yulianto (SUBSTANSI, 2017)
This study aims at analyzing national export financing transactions carried out by Indonesia Eximbank based on sharia principles. Although the number of sharia financing transactions increased significantly during the last five years, the percentage of sharia financing transactions is sigficantly lower than the conventional ones. As one of the largest moslems populations in the world and due to the global trend of sharia financing, Indonesia Eximbank should improve the quantity as well as the quality of sharia national export financing. This study is a descriptive qualitative study which analyze the sharia financing model conducted by Indonesia Eximbank during recent years. It also explain the variety of sharia agreement implemented by Indonesia Eximbank toward its customers. Based on the discussion results, Indonesia Eximbank should upgraded the sharia financing model from the existing Islamic window into Islamic subsidiary. Indonesia Eximbank also must improve the kind of sharia agreement considering the risks in sharia, legal, and operational aspects.